Relationship between D-dimer level and severity in COVID-19 cases at Dustira Hospital - Roslaeni, Rini; N Nawangsih, Eka; Judarisa, Tristy (ACTA Medical Health Sciences, 2023)
Coronavirus Disease-2019 (COVID-19) is an emerging disease with clinical symptoms similar to severe pneumonia. It is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). COVID-19 encompasses various degrees of severity, including mild, moderate, severe, and critical. One of the supporting tests used to detect COVID-19 is the D-dimer test. This cross-sectional study aims to investigate the relationship between D-dimer levels and the severity of COVID-19. The study was conducted at Dustira Hospital in West Java, Indonesia, from September 2022 to January 2023. D-dimer examination utilizes the Sysmex CS-2500 instrument, with a reference value of <0.5 mg/L. A sample of 42 patients was selected using the purposive sampling technique. The results revealed that the majority of confirmed COVID-19 cases were female (59.5%), with the highest proportion in the age groups of 41-50 years and 51-60 years (33.3%). Among the patients, 52.4% had moderate severity, and 64.3% had increased D-dimer levels. The average D-dimer levels in patients with moderate, severe, and critical symptoms were 0.97 mg/L, 2.33 mg/L, and 4.35 mg/L, respectively. The data were analyzed using the Kruskal-Wallis test, which indicated a significant difference in D-dimer levels based on the severity of COVID-19 (p=0.0001). Elevated D-dimer levels occur as a result of SARS-CoV-2 infection, which triggers an exaggerated inflammatory response leading to a cytokine storm. This, in turn, causes endothelial cell dysfunction and stimulates an excessive immune response, resulting in immune cells attacking healthy tissue. The severity of symptoms worsens as the D-dimer level increases. DOI : 10.35990/amhs.v2n2.p81-87 REFERENCE World Health Organization. WHO Official COVID-19 Info [Internet]. 2022 [cited 2022 Jul 17]. Available from: https://www.who.int/emergencies/diseases/novel-coronavirus-2019 Magdalena, Sugiri YJ, Tantular R, Listyoko A. Karakteristik Klinis Pasien COVID-19 di Rumah Sakit Dr. Saiful Anwar, Malang. J Respirol Indones. 2021;41(1):7–14. Susilo A, Rumende CM, Pitoyo CW, Santoso WD, Yulianti M, Herikurniawan H, et al. Coronavirus Disease 2019: Tinjauan Literatur Terkini. J Penyakit Dalam Indones. 2020;7(1):45–67. Kementerian Kesehatan RI. Peta Sebaran Transmisi Lokal dan Wilayah Terkonfirmasi [Internet]. [cited 2022 Jul 18]. Available from: https://infeksiemerging.kemkes.go.id/dashboard/covid-19 Burhan E, Susanto AD, Nasution SA, Eka G, Pitoyo Ceva W, Susilo A, et al. Pedoman Tatalaksana COVID-19. 4th ed. Jakarta: 2022. p. 1–10. Willim HA, Hardigaloeh AT, Supit AI. Koagulopati pada Coronavirus Disease-2019 (COVID-19): Tinjauan pustaka. Intisari Sains Medis. 2020;11(3):749–56. Akbar MNA, Rahardjo AM, Parti DD, Sakinah EN. Analisis Hubungan NLR, D-dimer dan Saturasi Oksigen dengan Derajat Keparahan COVID-19 di RSU Kaliwates Jember. J Agromed Med Sci. 2022;8(1):51–5. Yao Y, Cao J, Wang Q, Shi Q, Liu K, Luo Z, et al. D-dimer as a biomarker for disease severity and mortality in COVID-19 patients: A case control study. J Intensive Care. 2020;8(49):2–11. Nemec HM, Ferenczy A, Iii BDC, Ashley DW, Montgomery A. Correlation of D-dimer and Outcomes in COVID-19 Patients. Am Surg. 2022;88:2115–8. Afandi D. Kaidah dasar bioetika dalam pengambilan keputusan klinis yang etis. Majalah Kedokteran Andalas. 2017;40(2):111–21. Centers for Disease Control and Prevention. Provisional COVID-19 Deaths by Sex and Age. 2023. Neves MT, de Matos LV, Vasques AC, Sousa IE, Ferreira I, Peres S, et al. COVID-19 and aging: Identifying measures of severity. SAGE Open Med. 2021;9:1–6. Liu Y, Mao B, Liang S, Yang JW, Lu HW, Chai YH, et al. Association between age and clinical characteristics and outcomes of COVID-19. Eur Respir J. 2020;55(5). Kurnianto E, Putra DH, Fannya P, Dewi DR. Tinjauan karakteristik pasien dengan kasus positif COVID-19 di Puskesmas Kecamatan Matraman. Indones Health Inf Manag J. 2021;9(2):102–8. Khaerunnisa R, Rumana NA, Yulia N, Fannya P. Gambaran Karakteristik Pasien COVID-19 di Rumah Sakit Mekar Sari Bekasi Tahun 2020–2021. J Manaj Inf Kesehat Indones. 2022;10(1):72. Berger JS, Kunichoff D, Adhikari S, Ahuja T, Amoroso N, Aphinyanaphongs Y, et al. Prevalence and Outcomes of D-Dimer Elevation in Hospitalized Patients With COVID-19. 2020;(Oct):2539–47. Tang N, Li D, Wang X, Sun Z. Abnormal coagulation parameters are associated with poor prognosis in patients with novel coronavirus pneumonia. J Thromb Haemost. 2020;18(4):844–7. Roslaeni R. Telaah Pustaka: D-Dimer Pada Pasien COVID-19. Med Kartika. 2022;5(3):332–42. Atmaja KS, Wicaksana AAGOS, Putra IWAS, Putra WWS. Hubungan konsentrasi serum C-Reactive Protein dan D-dimer dengan derajat keparahan dan mortalitas pasien COVID-19. Intisari Sains Medis. 2021;12(2):680. Ardiani S, Tursinawati Y, Wahab Z. Hubungan D-Dimer dengan Ketahanan Hidup Pasien Covid-19 Derajat Berat-Kritis di RSUD Tugurejo Semarang. Health Med J. 2022;5(1):44–9.